A temporal–spatial hybrid dynamic algorithm strategy for inelastic earthquake response analysis of super high‐rise building structures. (4th August 2021) - He, Zheng; Ren, Zhinan; Qi, Zhe; Fu, Shaojun
Summary: Based on the understanding about the spatial distribution of plasticity development in super high‐rise building structures excited with strong earthquakes, a temporal–spatial hybrid dynamic algorithm (TSHDA) strategy is specifically proposed with the combination of the previously developed bilateral algorithm switch mechanism. The coupling response of partitioned subdomains and interfaces by the nodal partition strategy is solved using the iterative interfacial prediction–correction procedure. Four implicit and two explicit algorithms are selected and implemented on a finite element analytical platform, generating a total of eight alternative hybrid algorithms. A performance evaluation is carried out on a high‐rise reinforced concrete frame structure, and a super high‐rise frame core‐tube structure indicates that using the TSHDA strategy can achieve a more desirable balance among accuracy, stability, and efficiency. Such strategy is believed to be elaborately tailored for those mega structures with some strengthened stories distributed along height. The computational accuracy is well maintained by the bilateral algorithm switch which can substantially reduce the error accumulated in the determination of the incremental internal force vectors of subdomains and interfaces. The hybrid DKNR + CA algorithm, that is, the combination of the Krylov subspace accelerated Newton (KNR) algorithm with Chang's algorithm (CA), demonstrates comparatively desirable accuracy and superior efficiency.